2003
DOI: 10.1093/hmg/ddg200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correction of canine dystrophic epidermolysis bullosa mediated by retroviral vectors

Abstract: We have assessed the suitability of retroviral vectors for gene therapy of recessive dystrophic epidermolysis bullosa (RDEB) in dogs expressing a mutated collagen type VII. Isolation and analysis of the 9 kb dog collagen type VII cDNA identified the causative genetic mutation G1906S and disclosed the interspecies conservation of collagen type VII. Highly efficient transfer of the wild-type collagen type VII cDNA to both dog RDEB and human primary RDEB collagen type VII-null keratinocytes using recombinant vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 30 publications
1
63
1
4
Order By: Relevance
“…16 Using this animal model, it was demonstrated, in vitro, that conventional retroviral vectors efficiently transduce the dog collagen VII cDNA into the dystrophic EB keratinocytes and achieve permanent expression of the transgene with correction of the defects caused by recessive dystrophic EB. 17 Although a safety preassessment of a human transgenic skin may be feasible in the future (see below), a preclinical gene therapy study in large immunocompetent animals remains critical to define the precise specifications for future clinical trials. Thus, a preclinical study on RDEB golden retriever dogs will soon be conducted in France by the group led by Dr G Meneguzzi.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 99%
“…16 Using this animal model, it was demonstrated, in vitro, that conventional retroviral vectors efficiently transduce the dog collagen VII cDNA into the dystrophic EB keratinocytes and achieve permanent expression of the transgene with correction of the defects caused by recessive dystrophic EB. 17 Although a safety preassessment of a human transgenic skin may be feasible in the future (see below), a preclinical gene therapy study in large immunocompetent animals remains critical to define the precise specifications for future clinical trials. Thus, a preclinical study on RDEB golden retriever dogs will soon be conducted in France by the group led by Dr G Meneguzzi.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 99%
“…Transgenic cells have been created using retroviral, lentiviral, transposon, ⌽C31-based integrase vectors, or mini-genes. [5][6][7][8][9][10][11][12][13] The lesions in RDEB, however, are distributed over multiple and large areas of the body, both on external (skin) and internal (gastrointestinal) sites, which makes local treatments impractical and unable to target the global pathology associated with RDEB. Thus, as these measures provide only local and temporal relief from the RDEB pathology, we wanted to design a strategy with the potential for systemic and durable correction of col7 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This modification should offer new perspectives to the study of the tightly regulated miRNA turnover as reported for miR-122 or miR-141 (Katoh et al 2009;Kim et al 2011). Likewise, given the reported payload of pMSCV (Baldeschi et al 2003), we expect that 39 UTRs as long as 5 kb can be cloned in the miR-Sens vector and tested in target cells without loss of sensitivity. So far, we have prepared more than 40 39 UTRs with sizes ranging up to 3 kb without significant loss of titer.…”
Section: Discussionmentioning
confidence: 88%